Education dimensions relevant to successful electronic levy mobilization in resource-rich yet poor countries in Africa - Moses Kumi Asamoah; Edward Nketiah-Amponsah; Joseph Danquah Ansong; Boadi Agyekum (Cogent Business & Management, 2023)
First and foremost, the study explored why countries in Africa are rich in natural resources yet resort to e-levy legislation for more revenues. In addition, the study investigated dimensions of education needed to facilitate successful mobilization of e-levy revenue in resource -rich yet poor countries in Africa. Qualitative exploratory design, semi-structured interviews, judgmental and snowball sampling techniques were used for the study. Twelve (12) scholars from US (N = 3), Uganda (N = 3) Canada (N = 3), Ghana (N = 3) were interrogated. The paper was guided by the natural resource-cursed and social learning theories. Thematic analyses were used to analyse the data. It was found that although African countries are rich in natural resources yet they face challenges generating revenue from natural resources due to mismanagement, poor leadership and weak governance. They also find it difficult to mobilize revenues from e-levy too because of the informal nature of the economy, lack of financial inclusion, corruption, the disinterest of the public in the e-levy legislation as well as inadequate education on the e-levy concept. But the advanced economies are successful in generating revenue from e-levy. Proactive leadership and governance in managing natural resources, addressing mismanagement, and dealing with corruption and its negative effects are required to make things happen in Africa. African economies need to be more formalised and financial inclusion deepened. Proper accounting of state revenues to the citizenry must be enforced. E-levy education, civic education, digital literacy, ethics and legal education, can significantly contribute to the success of e-levy revenue generation in Africa.
Keywords: 650; dimensions of education; E-levy; natural resource-rich; poor countries in Africa